Second and subsequent tumours among 1927 retinoblastoma patients diagnosed in Britain 1951-2004 - MacCarthy, A; Bayne, A; Brownbill, P; Bunch, K; Diggens, N; Draper, G; Hawkins, M; Jenkinson, H; Kingston, J; Stiller, C; Vincent, T; Murphy, M (2013)
Background: Retinoblastoma is an eye tumour of childhood that occurs in heritable and non-heritable forms. In the heritable form, there is a predisposition to the development of non-ocular subsequent primary tumours (SPTs). Methods: This study included 1927 retinoblastoma patients diagnosed in Britain from 1951 to 2004. Ascertainment was through the (UK) National Registry of Childhood Tumours; cases were followed-up for the occurrence of SPTs. Standardised incidence ratios (SIRs) were calculated. Results: We identified 169 SPTs in 152 patients. The SIR analysis included 145 SPTs with cancer registrations from the years 1971 to 2009. These tumours occurred in 132 patients: 112 of the 781 heritable and 20 of the 1075 (presumed) non-heritable cases under surveillance at the start of this period developed at least one registered SPT. The SIRs for all tumours combined were 13.7 (95% confidence interval 11.3-16.5) in heritable cases and 1.5 (0.9-2.3) in non-heritable cases. The main types of SPT in the heritable cases were leiomyosarcoma, (31 cases; SIR 1018.7 (692.2-1446.0)), osteosarcoma (26 cases; SIR 444.6 (290.4-651.4)), and skin melanoma (12 cases; SIR 18.6 (9.6-32.4)). Conclusion: The risk of SPTs in heritable retinoblastoma is extremely high. This has important implications for the clinical follow-up and counselling of survivors and their families. © 2013 Cancer Research UK. All rights reserved.